N-heterocyclic germylene-metal adducts - Leong, Bi Xiang (2016)
The N-heterocyclic chlorogermylene and chlorostannylene of composition [L"E" ̈Cl] (E = Ge, Sn; L = PhC(NtBu)2) is a Lewis bases due to the stabilization of the metal centres’ empty orbitals being stabilized by the lone pair electrons on the nitrogen atom of the ligand. Further stabilization was reinforced by replacing the Cl atom by the bulky and electron-donating bis(trimethylsily)amide substituent to form [L"E" ̈N(SiMe3)2] (E = Ge, Sn). In order to demonstrate the Lewis basicity of these compounds, [LGeN(SiMe3)2] was reacted with Lewis acidic borane to afford the N-heterocyclic germylene-borane adduct [L{(Me3Si)2N}Ge→BH3] (3). Following the isolation of 3 to show the basicity of [LGeN(SiMe3)2], NHGe reacted with germanium(II) chloride and tin(II) chloride to yield the N-heterocyclic germylene-dichlorogermylene adduct, [L{(Me3Si)2N}Ge→GeCl2] (4) and the first N-heterocyclic germylene-dichlorostannylene adduct, [L{(Me3Si)2N}Ge→SnCl2] (5), respectively. In contrast, the N-heterocyclic stannylene, [LSnN(SiMe3)2] is unable to coordinate with borane, germanium(II) chloride and tin(II) chloride to form the corresponding adducts. Instead, ligand exchange reactions took place to afford the chlorogermylene [LGeCl] and chlorostannylene [LSnCl] respectively. Compound 3, 4 and 5 were characterized by single crystal X-ray diffraction, NMR spectroscopy, elemental analysis and melting point determination.